2021
DOI: 10.3390/ijerph18094457
|View full text |Cite
|
Sign up to set email alerts
|

Tired, Worried and Burned Out, but Still Resilient: A Cross-Sectional Study of Mental Health Workers in the UK during the COVID-19 Pandemic

Abstract: The burden of the COVID-19 pandemic on health systems and the physical and mental health of healthcare workers (HCWs) has been substantial. This cross-sectional study aims to assess the effects of COVID-19 on the psychological wellbeing of mental health workers who provide care to a vulnerable patient population that have been particularly affected during this crisis. A total of 387 HCWs from across a large urban mental health service completed a self-administered questionnaire consisting of socio-demographic,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 71 publications
5
78
1
5
Order By: Relevance
“…Healthcare providers around the world have been experiencing various levels of perceived pressure, anxiety, depression, burnout, and post-traumatic stress disorder (PTSD) during the COVID-19 outbreak since late 2019 [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 15 , 16 , 17 , 18 , 19 ]. Although the situation in Taiwan has not been as severe as in other countries, the present study still detected an increase in perceived pressure, physical and mental burden, and burnout among Taiwan prehospital healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare providers around the world have been experiencing various levels of perceived pressure, anxiety, depression, burnout, and post-traumatic stress disorder (PTSD) during the COVID-19 outbreak since late 2019 [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 15 , 16 , 17 , 18 , 19 ]. Although the situation in Taiwan has not been as severe as in other countries, the present study still detected an increase in perceived pressure, physical and mental burden, and burnout among Taiwan prehospital healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dramatic changes in the work environment, and elevated risk levels in hospital and prehospital settings have induced significant pressure, anxiety, depression, and burnout in healthcare workers during the COVID-19 pandemic [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. One study also suggested that building a supportive environment and resilience capability may be beneficial to alleviating stress, anxiety, and pressure during this period [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than half of mental healthcare workers (52%) experienced sleep problems during pandemics in the UK. 44 A study of 939 healthcare workers in Turkey during the first wave of the pandemic, 50% of participants reported sleep problems. 13 Poor sleep quality (PSQI ≥ 5) was identified at a rate of 75.2% in a study of 257 healthcare workers in Bahrain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that increased workload and perceived time pressure are the most significant job demands contributing to burnout among therapists (McCormack et al, 2018). As this feasibility study was conducted during the COVID-19 pandemic, these aspects were particularly important given that the pandemic has created additional workload and an increase in associated pressures among healthcare professionals (Pappa et al, 2021;Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%